A Novel Miniaturized Single-Layer Frequency Selective Surface With Triband Characteristics - Sangeetha Subbaraj; Shini Ramadoss; Sandeep Kumar Palaniswamy (International Journal of Antennas and Propagation)
This paper presents a single-layer triband frequency selective surface (FSS) for spatial filtering in wireless communication applications. The via-less convoluted geometry is adopted in the unit cell design to achieve a miniaturized profile of 0.048λ0 × 0.048λ0, where λ0 corresponds to the lowest operating frequency. The proposed design offers band-stop characteristics for three operating frequency ranges such as 1.6, 2.4, and 5 GHz. The rotational symmetry of the proposed design manifests polarization insensitivity. Also, the proposed FSS exhibits excellent angular stability performance up to 70° with a frequency deviation of less than 1%. The equivalent circuit model is the working principle of the proposed FSS design. The prototype of the proposed FSS is fabricated and the experimental results are validated with the simulated results. Thus, the proposed spatial filter is a suitable candidate for enhancing the security of wireless communication.